Allen Clothen papers - Clothen, Allen
Pass (1801 January 21) for the brigantine Two Nancys, license (1801 January 31) for the brigantine Two Isabellas (Duas Izabellinhas), and certifications (1801 September 9 and December 20) for the brigantine Two Bettys (Due Bettine), all of which sailed under Clothen.
Ship captain of Baltimore, Md.
Collection material in Portuguese, with Italian.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Two Bettys (Brigantine); Two Isabellas (Brigantine); Two Nancys (Brigantine); Ship's papers -- 19th century; Baltimore (Md.) -- Commerce -- Italy; Baltimore (Md.) -- Commerce -- Portugal; Italy -- Commerce -- United States; Portugal -- Commerce -- United States; Ship captains